1989
DOI: 10.1148/radiology.170.1.2521192
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lumbosacral intervertebral disk abnormalities on MR images in pregnant and asymptomatic nonpregnant women.

Abstract: The prevalence of lumbosacral intervertebral disk bulge and herniation on sagittal magnetic resonance (MR) images was determined in 45 pregnant subjects and 41 asymptomatic nonpregnant women of childbearing age. MR technique differed for the pregnant and nonpregnant groups. Fifty-three percent of pregnant and 54% of nonpregnant women had an abnormal disk (bulge or herniation) at one or more levels (L3-4, L4-5, or L5-S1). The difference was not statistically significant. There was also no significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
4

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(49 citation statements)
references
References 0 publications
2
43
0
4
Order By: Relevance
“…Both patient groups that were imaged in the initial studies [9,15] were symptomatic, and it is therefore not known whether such changes are identified in patients who have never experienced low back pain. Studies that have compared the MRI findings in both symptomatic and asymptomatic populations have not assessed Modic changes [2,4,12,25]. Toyone et al [24] studied patients with low back pain and vertebral end-plate changes classified as either Type A (low SI on T1-weighted sequences) or Type B (high SI on T1-weighted sequences), finding that Type A changes correlated with a greater degree of back pain and segmental hypermobility, while Type B changes were more common in patients with stable degenerative disc disease.…”
Section: Discussionmentioning
confidence: 99%
“…Both patient groups that were imaged in the initial studies [9,15] were symptomatic, and it is therefore not known whether such changes are identified in patients who have never experienced low back pain. Studies that have compared the MRI findings in both symptomatic and asymptomatic populations have not assessed Modic changes [2,4,12,25]. Toyone et al [24] studied patients with low back pain and vertebral end-plate changes classified as either Type A (low SI on T1-weighted sequences) or Type B (high SI on T1-weighted sequences), finding that Type A changes correlated with a greater degree of back pain and segmental hypermobility, while Type B changes were more common in patients with stable degenerative disc disease.…”
Section: Discussionmentioning
confidence: 99%
“…Back pain is reported by as many as 50-76% of all pregnant women, generally as a musculoskeletal response to the shifting centre of gravity, weight gain and hormonal factors responsible for ligamentous relaxation and changes in the pelvic joints [99,165,170].…”
Section: Sciatica In Pregnancymentioning
confidence: 99%
“…MRI without the use of gadolinium chelates now allows detailed evaluation of HDD without exposure of the fetus to the potential negative effects of ionising radiation [65,104]. Abnormal disk encountered in asymptomatic pregnant women as well as the high prevalence of anatomic abnormalities discovered in asymptomatic people highlight the importance of careful correlation of symptoms and findings at MRI [20,92,104,170]. In the presence of symptomatic HDD, elective caesarean section may be the preferred route of delivery with the anticipation that increasing epidural venous pressure, which is an indirect measure of CSF pressure, could precipitate progressive neurological dysfunction [103].…”
Section: Sciatica In Pregnancymentioning
confidence: 99%
“…Several tests have been described for examining the lumbar spine in pregnancy (Ostgaard et al 1994b;Sturesson et al 1997), but the test reaction, in terms of pain or stiffness, is not specific enough to exclude intervertebral disc pathology, which is probably the most common structural source of non-specific lumbopelvic pain (Bogduk 1995). There is no difference in the prevalence of disc abnormalities between pregnant and nonpregnant populations (Weinreb et al 1989). Many researchers rely on pain provocation tests for identifying PGP, though it has been suggested that the risk of a false positive is higher when no identification of discogenic pain is performed (Laslett et al 2003).…”
Section: Introductionmentioning
confidence: 99%